Genomic insights into an endophytic Streptomyces sp. VITGV156 for antimicrobial compounds - Veilumuthu, Pattapulavar; Nagarajan, T.; Magar, Sharayu; Sundaresan, Sasikumar; Moses, Lenus Joy; Theodore, Thomas; Christopher, John Godwin (Frontiers in Microbiology, 2024)
Endophytic Streptomyces sp. are recognized as a potential resource for valuable natural products but are less explored. This study focused on exploring endophytic Streptomyces species residing within tomato plants (Solanum lycopersicum) harboring genes for the production of a novel class of antibiotics. Our research involved the isolation and characterization of Streptomyces sp. VITGV156, a newly identified endophytic Streptomyces species that produces antimicrobial products. VITGV156 harbors a genome of 8.18 mb and codes 6,512 proteins, of which 4,993 are of known function (76.67%) and 1,519 are of unknown function (23.32%). By employing genomic analysis, we elucidate the genome landscape of this microbial strain and shed light on various BGCs responsible for producing polyketide antimicrobial compounds, with particular emphasis on the antibiotic kendomycin. We extended our study by evaluating the antibacterial properties of kendomycin. Overall, this study provides valuable insights into the genome of endophytic Streptomyces species, particularly Streptomyces sp. VITGV156, which are prolific producers of antimicrobial agents. These findings hold promise for further research and exploitation of pharmaceutical compounds, offering opportunities for the development of novel antimicrobial drugs.